Impact of social media news on COVID-19 vaccine hesitancy and vaccination behavior. (May 2023) - Zhang, Qianyao; Zhang, Runtong; Wu, Wen; Liu, Yang; Zhou, Yu
Highlights: Compared to safety news, individuals are more sensitive to vaccine risk news from social media. Safety perception and risk perception are critical psychological factors behind vaccine hesitancy. Ego network density mitigates the link between social media vaccine news and vaccine perceptions. Abstract: In order to take advantage of the power of social media to promote vaccination, this study reveals the mechanisms of positive and negative impacts of social media news on vaccine hesitancy and vaccination behavior. Based on the stimulus-organism-response (S-O-R) framework, we developed a research model to understand the effects of vaccine safety news and risk news from social media (external stimuli) on individuals' psychological organism (i.e., safety perception and risk perception) and consequent behavioral response, vaccine hesitancy and vaccination behavior. The proposed model was tested by partial least square structural equation modeling (PLS-SEM) on a sample gathered in China from September 2021 to November 2021 and from February 2022 to April 2022 (valid responses = 1579). The results found that the relationship between vaccine risk news from social media and risk perception was higher than the relationship between vaccine safety news from social media and safety perception. Individuals are more sensitive to vaccine risk news than safety news on social media. Moreover, both safety perception and risk perception explained the critical psychological mechanisms behind vaccine hesitancy. Interestingly, ego network density mitigated the effect of safety news on safety perception and the effect of risk news on risk perception. The findings contribute to the S-O-R model, the research on social media effects, and the literature on vaccination attitudes and behaviors. This study also informs public health officials about leveraging the power of social media to motivate the public to accept the COVID-19 vaccines.